Synthesis and characterization of zinc oxide supported on mesoporous hollow silica sphere for photocatalysis of sodium dodecylbenzenesulfonate - Pourdayhimi, Parisa (2016)
With the increasing demands of higher living standard accompanied by ever growing of world population and industrial process, the consumption of organic chemicals has been increasing. Most of organic compounds are difficult to be degraded by means of biological and chemical decompositions, making serious damages to the environment. Sodium dodecylbenzenesulfonate (SDBS) is one of the most common surfactants widely used in manufacturing of cleaning products. It can be decomposed through photocatalysis. Among the reported photocatalysts, ZnO is considered as cheap, environmentally friendly and biocompatible material with band gap energy of 3.37 eV. However, the ZnO has low photocatalytic activity due to the formation of aggregates. In this research, a new photocatalyst of zinc oxide immobilized in mesoporous hollow silica spheres (ZnO-MHSSs) have been synthesized for photocatalytic degradation of SDBS under ultraviolet irradiation. ZnO-MHSSs were synthesized via impregnation method applying different temperatures (50 and 85ºC) and ZnO loadings. Zinc acetate dihydrate and tetraethyl orthosilicate were used as precursors of zinc oxide and silica, respectively. In the first attempt, the MHSS was loaded with ZnO (Zn:Si = 1:15, 1:30 and 1:50) at 85ºC. X-ray diffraction (XRD) analysis results confirmed the attainment of mesoporous structure for the obtained composite materials. Nitrogen adsorption-desorption analysis also depicted the formation of mesoporous structure and high surface area for the ZnO-MHSSs compared to bare ZnO. Field emission scanning electron microscopy showed uniform spheres for all samples. The photocatalysis testing was carried out for ZnO-MHSS, ZnO and MHSS by using aqueous solutions of SDBS. The photocatalytic efficiency was determined through tracing the maximum absorption difference of SDBS at fixed time intervals of reaction by using an ultraviolet spectrophotometer. The photocatalysis results demonstrated 14.2-21% efficiency improvement of SDBS decomposition. Applying higher molar ratio of Zn/Si, resulted in formation of zinc silicate (willemite) phase which is not favourable. Therefore, a second procedure was employed in investigating the effect of the higher molar ratio. In the second attempt, ZnO-MHSSs (Zn/Si: 1:1, 1:2, and 2:1) were synthesized at a lower temperature of 50ºC without applying calcination. The XRD analysis confirmed the successful formation of zinc oxide which is not accompanied with the existence of zinc silicate, willemite. Study of the photocatalysis performance was carried out over the prepared samples. The results showed the successful decomposition of SDBS with the highest photocatalytic efficiency improvement (26.7%) for Zn/Si: 1:1 as the best photocatalyst.